Offshoring and the onshore composition of tasks and skills - Sascha O. Becker; Karolina Ekholm; Marc-Andreas Muendler (Institut für Angewandte Wirtschaftsforschung (IAW), 2009)
We analyze the relationship between offshoring and the onshore workforce composition in German multinational enterprises (MNEs), using plant data that allow us to discern tasks, occupations, and workforce skills. Offshoring is associated with a statistically significant shift towards more non-routine and more interactive tasks, and with a shift towards highly educated workers. Moreover, the shift towards highly educated workers is in excess of what is implied by changes in either the task or the occupational composition. Whether offshored activities are located in low-income or high-income countries does not alter the direction of the relationship. We find offshoring to predict between 10 and 15 percent of observed changes in wage-bill shares of highly educated workers and measures of non-routine and interactive tasks.
Keywords: F16; F14; F23; J23; J24; 330; Trade in tasks; multinational enterprises; demand for labor linked employer-employee data; Arbeitsnachfrage; Offshoring; Arbeitskräfte; Qualifikation; Multinationales Unternehmen; Deutschland